PERCEPTION AND INTENTION USING IMPLANT AS CONTRACEPTION IN DESA NGASEM KEDIRI - Shinta Kristianti; Mika Mediawati; Dewi Rohmawati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
The most effective family planning program used for fertile age couple is long phase contraception. The use of long term contraception did not face the target, it is still dominate by short term contraception. The use of long term contraception such as Implant was not enthused in Ngasem Kediri. The aim of this research to know the relationship between motherâ€™s perception with interest in using implant as contraception in Ngasem Kediri. It used a survey analytic research design with cross sectional approach. The population was women who used condom as contaception and the unmet need. It was taken 52 respondents. The data collecting used was questionnaire. The research result showed the respondents who had positive perception with low interest were 27 respondents (58,7%). Bivariate Analysis result by Chi Square showed Ïvalue result was 0,000. So there was a relationship between motherâ€™s perception with interest in using implant as concraception in Ngasem Kediri .